Psychiatry and homoeopathy - Davidson, Jonathan (British Homeopathic Journal, 1994)
A comparison is made between psychiatry and homoeopathy, with reference to five homoeopathic principles. These are the law of similars, the self-healing principle, the microdose effect, Hering's Law and diagnosis through pattern recognition. There is evidence that all of these have been incorporated into contemporary psychiatry, and that recent neurobiological research provides a measure of validation to these age-old teachings. Some testable research questions are also proposed.
Keywords: Psychiatry; Homoeopathy; Law of similars; Self-healing; Microdose; Hering's Law; Rollback; Pattern recognition